A clinical study on the efficacy and safety of the exopolymers from Aureobasidium pullulans (EAP) in subjects with mild-to-moderate atopic dermatitis - Park, Hye-Su; Kang, Minseo; Kim, Yong-Min; Lim, Jong-Min; Kim, Young Suk; Kim, Hee-Taek; Choi, Jae-Suk (Toxicology and environmental health sciences, 2020)
Objective This study aimed to investigate the efficacy and safety of the exopolymers from Aureobasidium pullulans (EAP) in subjects with mild-to-moderate atopic dermatitis. Methods A total of 68 subjects who visited Semyung Oriental Medical Center from November 16, 2015, to September 8, 2016, were included in the study. The subjects were treated orally with EAP (250 mg/day; experimental group) or placebo (control group) for 12 weeks. A series of clinical examinations, hematological assessments, blood biochemistry, urinalysis, and skin assessments were conducted at baseline and after the study period to evaluate efficacy and safety. The primary endpoint was the Severity Scoring of Atopic Dermatitis (SCORAD) index. Results A significantly greater reduction of SCORAD index as a primary endpoint showed in the treatment group than in the placebo group ( p = 0.0053) during the treatment period. The secondary endpoints of serum interferon-γ levels, skin hydration, and transepidermal water loss showed significant changes over time within the EAP group. Other secondary endpoints showed no statistically significant changes. Safety evaluations identified no abnormal changes within the experimental or placebo groups. Conclusions These experiments indicated that it was safe to ingest this dose of EAP orally for 12 weeks and that this treatment could help to alleviate atopic dermatitis.